Yield behavior of random copolymers of isotactic polypropylene. (27th October 2017) - Auriemma, Finizia; De Rosa, Claudio; Di Girolamo, Rocco; Malafronte, Anna; Scoti, Miriam; Cipullo, Roberta
Abstract: The crystallographic micromechanical model (CMM) for prediction of yield stress of semicrystalline polymers, based on the thermally activated nucleation of screw dislocations at the boundary of lamellar crystals, is employed to interpret the yield behavior by effect of uniaxial drawing of some isotactic copolymers of propylene with different comonomeric units such as ethylene, 1-butene, 1-pentene, 1-hexene, and 1-octadecene (iPPEt, iPPBu, iPPPe, iPPHe and iPPOc, respectively). The samples are characterized by a random distribution of the comonomeric units. The CMM predicts that the values of stress at yield depend on the thickness of the lamellar crystals and relies on two parameters, i.e. the critical value of the free energy needed for nucleation and activation of a screw dislocation in crystallographic planes parallel to the chain axes, and the shear modulus relative to the planes of slip for the dislocations, whereas the role of the interlamellar amorphous phase is neglected. The aim of this study is to analyze to which extend the thickness of the lamellar crystals influences the yield stress for a series of propylene-based copolymers having a well-defined chain microstructure and crystallized in the α and/or γ forms, but possessing different degree of crystallinity, thickness of the lamellar crystals, stability of the crystals and also intrinsic flexibility of the portions of chains belonging to the amorphous regions, in relation with the degree of inclusion (exclusion) of the co-monomers in (from) the crystals. It is shown that, in the case of copolymers with a comonomer concentration lower than a threshold, the yield stress increases with increasing the lamellar thickness regardless of type of comonomer, the relative amount of the two polymorphs (α and γ forms), and the degree of inclusion, in good agreement with the predictions of the CMM approach. For copolymers with comonomer concentration higher than a threshold and bulky side groups, which are excluded from the crystals, the thickness of the lamellar crystals becomes low and the role of the chains in the amorphous regions becomes not negligible. In the case of copolymers with high butene concentration, instead, the stress at yield decreases with increasing the thickness of the lamellar crystals, because the high degree of inclusion of butene units in the crystals induces not only an increase in the thickness of the lamellar crystals, but also a decrease in the stability of the crystals, and the role of the chains located in the interlamellar amorphous layers acting as tie-molecules may not be disregarded. Graphical abstract: Highlights: In isotactic copolymers of propylene, comonomers may be or not included in the crystals. The yield behavior of these copolymers is controlled by the degree of inclusion/exclusion. For low or no inclusion, the stress at yield increases with increasing the lamellar thickness l c . For propylene/butene copolymers the stress at yield decreases with increase of l c due to inclusion. A Crystallographic Micromechanical Model approach is used to rationalize the data.